The Use of Problem-Based Learning Physics E-Module on Global Warming Material: High School Students Perception - Wilson, Julius; Mole, Paulina Nelce; Dua Riong, Maria Bernadetha (Journal of Innovative Science Education, 2023)
Global warming as one of the physics materials, is a topic that tends to beabstract so it causes difficulties for students. In addition, limited time forlearning activities in class is an obstacle to achieving optimal understanding.Lack of learning time in class can limit students' exploration space. The use ofe-modules based on Problem-Based Learning is an innovative solution tovisualize the phenomenon of global warming through images, videos,animations, and simulations. Limited learning time in class can be overcomethrough the flexibility of using e-modules. The purpose of this study is todescribe the perception of high school students towards the use of ProblemBased Learning physics-based e-modules on global warming material. Emodules are designed to stimulate student learning by utilizing a problembased learning model, where real-life problems are integrated into learning.This research was conducted with a qualitative approach. The subjects of thisstudy were students of St. Gabriel Maumere Catholic High School. Theresearch instruments used are perception questionnaire sheets, documentation,and interviews. The results showed that the percentage of student perceptionon the e-module display indicator was 85.25%, the presentation of material inthe e-module was 82.68% and the overall benefits of the e-module were verygood. Based on the results of data analysis through questionnaires andinterviews, students gave a very good perception of the e-module on globalwarming material.